Design of Monitoring and Control of Energy Use in Multi-storey Buildings based on IoT - Arief Wisaksono; Yanik Purwanti; Novia Ariyanti; Masruchin Masruchin (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2020)
This study discusses monitoring and control systems. Energy use in buildings or high-rise buildings based on IoT. In general, standard buildings are designed and built without regard to automation with supporting technology, namely a system installed to control and monitor the building services responsible for lighting, cooling, electricity. and others IOT-based energy monitoring and control using two serial communication systems run together which are managed by the Blink application using two micro controllers in one package, one microcontroller for monitoring and detecting how much electrical energy is used continuously with fixed looping and another microcontroller for sensor control, so that the automation system can turn on and turn off the electrical energy that is supplied to each floor. Lined serial communication systems are used to ensure system continuity, by using this communication system the control can be done right The results obtained from the process are monitoring and controlling energy both AC lights or other usage in real time